2016
DOI: 10.1080/09537325.2016.1220515
|View full text |Cite
|
Sign up to set email alerts
|

Combining the technological innovation systems framework with the entrepreneurs’ perspective on innovation

Abstract: For their technological sustainability innovations to become successful, entrepreneurs can strategically shape the technological field in which they are involved. The technological innovation systems (TISs) literature has generated valuable insights into the processes which need to be stimulated for the successful development and implementation of innovative sustainability technologies. To explore the applicability of the TIS framework from the perspective of entrepreneurs, we conducted a case study in the Dut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(69 citation statements)
references
References 36 publications
3
66
0
Order By: Relevance
“…Furthermore, as another confirmation of the findings of Planko et al [44,63], the role of experts, expertise and knowledge is of key importance, resonating with Thornton's institutional order of profession [65]. This may be well understood from a system-building perspective: as Hekkert et al [42] argue, knowledge is essential to provide further guidance to the search process, and thus relating the innovation to knowledgeable actors and sources of knowledge (development) is of key importance.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Furthermore, as another confirmation of the findings of Planko et al [44,63], the role of experts, expertise and knowledge is of key importance, resonating with Thornton's institutional order of profession [65]. This may be well understood from a system-building perspective: as Hekkert et al [42] argue, knowledge is essential to provide further guidance to the search process, and thus relating the innovation to knowledgeable actors and sources of knowledge (development) is of key importance.…”
Section: Discussionsupporting
confidence: 78%
“…Based on innovation system literature, we may add to strategic leadership literature that the ways in which these features matter may be understood by stating that they are part of efforts of system-building, especially regarding legitimacy creation and market formation. In line with the findings of Planko et al [44,63], we have found that joint vision and ambition [T1] are of key importance: they mobilize, both internally and externally, others [R2, T2] by indicating how a wicked problem may be fruitfully solved, and they provide orientation [R3] and legitimacy [R4] to the collective action implied in the systemic innovation. Collaborative/relational processes are important to generate trust or legitimacy [R4].…”
Section: Discussionsupporting
confidence: 72%
“…For example, Bergek, Jacobsson, and Sandén (2008) and Markard and Truffer (2008a) underline the importance of managerial perspective in the innovation system and relate literature on innovation systems to literature on business studies and innovation management. Only recently, a first conceptualisation of TIS as strategic management framework was made by Planko et al (2016), who investigated to what extent entrepreneurs recognised the functions of TIS in the development and implementation of their technological innovation. Indeed, the entrepreneurs acknowledged the importance of all functions in their daily work, although the prominence of specific functions varied.…”
Section: Functional Approach Of Tis: From Policy To Strategic Managementmentioning
confidence: 99%
“…Indeed, the entrepreneurs acknowledged the importance of all functions in their daily work, although the prominence of specific functions varied. However, Planko et al (2016) only focused on one sector (smart grids), and did not systematically address the interactional processes involved in the functions. To further scrutinise the applicability of TIS in the management domain, these processes should be the starting point, rather than entrepreneurs' recognition of the functions.…”
Section: Functional Approach Of Tis: From Policy To Strategic Managementmentioning
confidence: 99%
See 1 more Smart Citation